Chemical and botanical indicators of groundwater inflow to Sphagnum-dominated peatlands. (May 2016) - Larocque, M.; Ferlatte, M.; Pellerin, S.; Cloutier, V.; Munger, J.L.; Paniconi, C.; Quillet, A.
Abstract: Knowledge of whether a peatland is fed by a surface aquifer or is providing water to the aquifer can lead to different aquifer and wetland management strategies. Few studies have been conducted to investigate aquifer-peatland connections, because flow connections are difficult to measure and can be spatially and temporally variable. The objective of this study was to combine chemical and botanical indicators of groundwater inflow to Sphagnum -dominated peatlands for a better classification of their water sources. Available knowledge of peatland geomorphic setting, water chemistry, and vegetation data for 12 aquifer-peatland systems of the Abitibi-Temiscamingue region and of the St. Lawrence Lowlands, two contrasting regions of southern Quebec (Canada), were used to derive indicators of groundwater inflow. Total dissolved solids (TDS) is identified as a comprehensive indicator of water mineralization. Threshold values of 16 mg/l (Abitibi-Temiscamingue) and 22 mg/l (St. Lawrence Lowlands) were found to indicate the presence of groundwater within the peatland. Results show that combining chemical (TDS) and botanical indicators can detect the presence of groundwater inflow into most of the studied peatlands. The indicators are more efficient on slope peatlands, where groundwater inflow is more substantial and less spatially variable, than in basin peatlands. A two-step approach is proposed: (1) identify the geomorphic setting of the peatland, and (2) estimate the chemical and botanical indicators. This approach is low-cost and easy to implement, and thus can be used on a large number of sites to assess the presence of groundwater inflow to peatlands.